A Study on Using Glass Fiber-Reinforced Polymer Composites for Shear and Flexural Enhancement of Reinforced Concrete Beams - Hibretu Kaske Kassa; Getinet Melesse; Gashahun Yabasa (Advances in Civil Engineering)
In the concrete construction sector, issues such as tensile strength of structural elements, brittle mode of failure, rapid crack propagation, and increased overload are common. The experimental evaluation of the flexural strengths of glass fiber-reinforced polymers with various percent of glass fiber content is the focus of this study. Fiber-reinforced polymer is the focus of numerous studies right now all over the world. Experimental investigations done on the behavior of the concrete strengthened using discontinuous chopped glass fiber were carried out with C-25 concrete mix and 50 mm of glass fiber at various percentages (0.25%, 0.50%, 0.75%) of addition by the total weight of concrete. Experimental data on load for flexural tests have been carried out. Strength variations and failure modes of each specimen have been obtained. According to ASTM standards, at 7, 21, and 28 days after casting, all beams, such as control and fiber-reinforced concrete beams, are tested by third point loading. The results of the flexural test indicated that the presence of glass fiber tends to increase the flexural strength of concrete at higher fiber content, and the bending test results indicated that the modulus of rupture of concrete in set I increases by 2.5% at 0.25% glass fiber, 11.3% at 0.50% glass fiber, 13.2% at 0.75% glass fiber at the end of 7 days, 1.19% at 0.25% glass fiber, 2.38% at 0.50% glass fiber and 9.94% at 0.75% glass fiber at the end of 21 days, 0.54% at 0.25% glass fiber, 1.89 at 0.50% glass fiber, and 2.45% at 0.75% glass fiber at the end of 28 days. Thus, ductility improves after concrete cracking, with 2.19% at 0.25% glass fiber, 10.19% at 0.50% glass fiber, and 13.60% at 0.75% glass fiber at the end of 28 days. As a result, the flexural strength of the content improves as well.